Correlation between migraine subtipes and depression Correlação entre subtipos de migrânea e depressão - Renan Barros Domingues; Esther Angélica Coelho Costa; Ariovaldo da Silva Jr; Simone Aires Domingues; Juliana Cardoso Leal; Rodrigo Santiago Gomez; Antônio Lúcio Teixeira Jr (Arquivos de Neuro-Psiquiatria)
This study has evaluated depression in patients with episodic migraine (n=98), chronic migraine without medication overuse (n=23), and chronic migraine with medication overuse (n=57). The Beck Depression Inventory (BDI) was used to evaluate depressive symptoms in these three groups. The mean BDI score obtained in all patients was higher than that observed in asymptomatic subjects (episodic migraine=16.09±11.79, chronic migraine with medication overuse=18.91±12.53, chronic migraine without medication overuse=19.83±14.79). This finding corroborates previous studies suggesting a co-morbid association between migraine and depression. Depression did not seem to be crucial in the transformation of migraine as the median BDI scores did not differ significantly between patients with episodic and chronic migraine. The median BDI scores of the patients with chronic migraine with medication overuse and that patients with chronic migraine without medication overuse were similar as well. Therefore, medication overuse behavior may not be related with depression. Este estudo avaliou a depressão em pacientes com migrânea episódica (n=98), migrânea crônica com uso abusivo de analgésicos (n=57) e migrânea crônica sem uso abusivo de medicamentos analgésicos (n=23). O Inventário de Depressão de Beck (IDB) foi usado para avaliar sintomas depressivos nos três grupos. As médias dos escores de IDB encontradas (migrânea episódica=16.09±11.79, migrânea crônica com uso abusivo de analgésicos=18.91±12.53, migrânea crônica sem uso abusivo de analgésicos=19.83±14.79) foram maiores do que as observadas em indivíduos assintomáticos. Tais resultados confirmam estudos prévios indicando uma relação de comorbidade entre migrânea e depressão. Os dados não sugerem que a depressão seja um fator determinante da transformação da migrânea episódica em migrânea crônica, pois nestes dois grupos as medianas dos escores de IDB foram semelhantes. Os escores de IDB foram semelhantes entre os pacientes com migrânea crônica com e sem uso abusivo de analgésicos. Portanto, o comportamento de ingerir abusivamente analgésicos não parece estar relacionado com a depressão.